Combining Ultrasound-Guided Popliteal Sciatic and Adductor Canal Block as a Lifesaver for High-Risk Patients Scheduled for Emergency Below Knee Surgery: A Case Series - Vijayalaxmi Biradar; Shweta Konnur; Abhay Sancheti (Archives of Anesthesia and Critical Care)
High risk patients with multiple comorbidities, sepsis, poor cardiopulmonary reserve when posted for emergency below knee surgeries definitely pose challenges in terms of Anaesthesia. In this case series we highlighted the important role of ultrasound guided popliteal sciatic combined with adductor canal block as a sole anaesthetic technique for safe outcome in high risk cases having significant and multiple comorbidites. 10 cases with ASA physical status III and IV, aged 50-70 years scheduled for below knee surgeries were enrolled. All the patients received ultrasound guided popliteal sciatic nerve block with 8 ml of 2% Lignocaine with Adrenaline and 8 ml of 0.5% of Bupivacaine and 4mg Dexamethasone (1ml) (total volume 17 ml) and Adductor canal block with 8 ml of 0.5% of Bupivacaine. Adequate sensory and motor blockade required for surgery was achieved, with stable haemodynamic parameters throughout the procedure. No patient developed any serious complication in the perioperative period. Combination of the popliteal sciatic nerve and adductor canal block provide sufficient sensory and motor block with good hemodynamic stability for below-knee surgeries. When used on high-risk patients with numerous comorbidities, this anesthetic technique has the potential to save lives.